Complex Service Desk System for Incident Management Automation - Michal Dostál (Computing Open)
Lengthy waiting times and repetitive, routine requests can detrimentally impact the operational efficiency of the Service Desk department, ultimately jeopardizing customer loyalty to the company. This paper advocates for a conceptual artifact within the Service Desk system, comprising multiple integrated systems to form a comprehensive solution for efficient incident management. The envisioned Service Desk system incorporates a virtual assistant to streamline fundamental incident management activities, leveraging technologies like customer intent detection, expert systems, and an expertise locator system to enhance ticket resolution efficiency. This proposed system’s design adheres to the principles of the design science methodology. To assess both the identified problem area and the efficacy of the proposed artifact, ex-ante evaluation methods were employed, specifically through focus group discussions. The envisioned artifact not only addresses the immediate challenges but also contributes to the broader adoption of knowledge management tools in IT service management. The potential implications of implementing this artifact extend to Service Desk departments, fostering increased effectiveness in incident management practices and information flow. This, in turn, holds promise for an overall improvement in the efficiency and responsiveness of Service Desk operations, positively impacting customer satisfaction and loyalty.